(untitled) (Mūzikas akadēmijas raksti, 2024)
In 1872 the Latvian schoolteacher and composer Jānis Cimze (1814–81) published, in Leipzig, a two-volume collection of four-part choral works entitled A Garland of Songs (Dziesmu rota). Its first volume, Garden Flowers (Dārza puķes), contained a selection of works widely known from the repertory of the German choral movement of the early and mid-nineteenth century, with texts newly translated into Latvian. Its second volume, Wild Flowers (Lauka puķes), contained eighty-six Latvian folksong melodies arranged for four voices by Cimze and a handful of his Livland colleagues. Over the course of the following decades, Cimze’s Wild Flowers would emerge as one of the seminal texts in the history of Latvian nationalism, widely acknowledged among his contemporaries as one of the most powerful expressions of Latvian national sentiment articulated during the period. Indeed, the arrangements it contained would form the core repertoire of the First All-Latvian Song Festival of 1873.